Aromatherapy Ginger Use in Patients with Nausea & Vomiting on Post Cervical Cancer Chemotherapy (KEMAS: Jurnal Kesehatan Masyarakat, 2017)
Chemotherapy is an effective treatment for cancer.  However, it causes some side effects which include nausea and vomiting. More than 70% of patients experience nausea and vomiting after chemotherapy. The purpose of this study was to determine the effect of ginger aromatherapy in nausea, and vomiting patients on post cervical cancer chemotherapy. We used a pretest-posttest control group design, using purposive sampling of 60 respondents. We used anti-emetics measurement tool according to Multinational Association of Supportive Care in Cancer (MASCC) to assessed patient’s complaints. The result showed significant difference in nausea and vomiting group before and after given aromatherapy (p = 0.000); nausea score (p = 0.005) and vomiting score (p= 0.013) from intervention and control group.  No significant difference was observed in nausea (p = 0.279), and vomiting (p = 0.276) on control group. Ginger aromatherapy can be used as alternative medication to reduce post-chemotherapy nausea and vomiting.